A Novel Clustering Routing Protocol in Wireless Sensor Network - Wu Rui; Xia Kewen; Bai Jianchuan; Zhang Zhiwei (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The phenomenon of network resource-constrained often appears in wireless sensor network (WSN) because of nodes with energy-limited, so it becomes a research topic to study on high-performance routing protocol in wireless sensor network. In accordance with the characteristic of quantum particle swarm optimization (QPSO), a novel clustering routing protocol with QPSO algorithm is proposed based on the low energy adaptive clustering hierarchy (LEACH), which includes several steps, such as determining the number of cluster-head, preliminary clustering, optimization on temporary cluster by QPSO algorithm, clustering after optimization, and so on. Comparative analysis on simulation experiments show that the proposed routing protocol is superior to that of LEACH, and saves energy consumption of network excellently and balances energy of nodes so as to prolong the life of the network.